PEMBANGUNAN PARIWISATA MELALUI MODEL PENTAHELIX: STUDI KASUS PASIR PUTIH KEPULAUAN KANGEAN - Auliyani, Alya; Haris, Rillia Aisyah (PUBLIC CORNER, 2024)
White sand beaches offer significant tourism potential, promising economic growth and development opportunities for local communities. This tourism development can improve community welfare through various sectors, such as tourism, hospitality and culinary. However, this large white sand tourism potential has not been utilized optimally due to lack of attention from stakeholders, including the government. The pentahelix model, which involves academics, government, business, community and media, is considered the right solution to optimize this tourism potential. This research aims to analyze the tourism potential of white sands and examine the role of the pentahelix model in its development. The research method used is literature study and direct field observation on white sand beaches. The results of the research show that tourism development is not yet optimal because there are no real shortages that have not been maximized by each stakeholder, they do not yet know the results of tourism development. Keywords: Pentahelix model, tourism development, Pasir Putih Beach